Natural selection on cork oak: allele frequency reveals divergent selection in cork oak populations along a temperature cline - Ramírez-Valiente, J. a; Lorenzo, Z.; Soto, A.; Valladares, F.; Gil, L.; Aranda, I. (Evolutionary Ecology, 2010)
A recent study of population divergence at neutral markers and adaptive traits in cork oak has observed an association between genetic distances at locus QpZAG46 and genetic distances for leaf size and growth. In that study it was proposed that certain loci could be linked to genes encoding for adaptive traits in cork oak and, thus, could be used in adaptation studies. In order to investigate this hypothesis, here we (1) looked for associations between molecular markers and a set of adaptive traits in cork oak, and (2) explored the effects of the climate on among-population patterns in adaptive traits and molecular markers. For this purpose, we chose 9-year-old plants originating from thirteen populations spanning a broad range of climatic conditions. Plants established in a common garden site were genotyped at six nuclear microsatellites and phenotypically characterized for six functional traits potentially related to plant performance. Our results supported the proposed linkage between locus QpZAG46 and genes encoding for leaf size and growth. Temperature caused adaptive population divergence in leaf size and growth, which was expressed as differences in the frequencies of the alleles at locus QpZAG46.
Keywords: Adaptation; Additive effects; Dominance; Natural selection; Overdominance; Quercus suber

Detection of hybrids in nature: application to oaks (Quercus suber and Q. ilex). - Burgarella, C.; Lorenzo, Z.; Jabbour-Zahab, R.; Lumaret, R.; Guichoux, E.; Petit, R. J.; Soto, A.; Gil, L. (Heredity, 2009)
Powerful and accurate detection of first-generation (F1) hybrids and backcrosses in nature is needed to achieve a better understanding of the function and dynamics of introgression. To document the frequency of ongoing interspecific gene exchange between two Mediterranean evergreen oaks, the cork oak (Quercus suber) and the holm oak (Q. ilex), we analyzed 1487 individuals originating from across the range of the two species using eight microsatellite loci and two Bayesian clustering approaches (implemented in the programs STRUCTURE and NEWHYBRIDS). Simulated data were used to assess the differences between the two clustering methods and to back up the choice of the threshold value for the posterior probability to discriminate admixed from pure individuals. We found that the use of STRUCTURE resulted in the highest power to detect hybrids, whereas NEWHYBRIDS provided the highest accuracy. Irrespective of the approach, the two species were clearly distinguished as independent genetic entities without any prior information. In contrast with previous reports, we found no evidence for unidirectional introgression. The overall hybridization rate was very low (<2% of introgressed individuals). Only two individuals were identified as F1 hybrids and five as early backcrosses. This work shows that the combined application of the two complementary Bayesian approaches and their systematic validation with simulations, fit for the case at hand, helps gain resolution in the identification of admixed individuals.
The following values have no corresponding Zotero field: accession-num: 19240752
Keywords: clustering analysis; introgressive hybridization; microsatellites; Q. ilex; Quercus suber; Simulation

Molecular and palaeoecological evidence for multiple glacial refugia for evergreen oaks on the Iberian Peninsula (Journal of Biogeography, 2007)
Aim A multiple glacial refugia hypothesis for Mediterranean plant species was tested with the evergreen Quercus complex (Quercus suber L., Quercus ilex L. and Quercus coccifera L.) from the Iberian Peninsula, using molecular and palaeobotanical data. Location The Iberian Peninsula, which is an ecologically and physiographically complex area located on the western edge of the Mediterranean Basin. Methods We sampled 1522 individuals from 164 populations of Q. suber, Q. ilex and Q. coccifera. A review of the recent literature on fossil pollen and charcoal records and a nested clade analysis on chloroplast DNA polymerase chain reaction-restriction fragment length polymorphism was carried out to infer demographic and historical processes. Results The analysis indicates at least one glacial refugium for Q. suber in southwestern Iberia. Extensive introgression of Q. suber with Q. ilex indicates several potential refugia in eastern Iberia. Past fragmentation was followed by a restricted range ﬂow/range expansion, suggesting multiple refugia for Q. ilex–Q. coccifera elsewhere in central and northern Iberia and multiple areas of secondary contact. This ﬁnding is consistent with fossil records. Main conclusions The predicted multiple refugia during glacial periods indicates the existence of secondary post-glaciation contact areas. These areas contained complex diversity patterns resulting mainly from range expansions followed by isolation by distance. To a lesser degree, traces of restricted and longdistance dispersal were also found.

Formation of Acutissimin A in red wine through the contact with cork - Gil, L.; Pereira, C.; Branco, P.; Teixeira, A. (JOURNAL INTERNATIONAL DES SCIENCES DE LA VIGNE ET DU VIN, 2006)
This study shows that when cork material gets in contact with wine, the elagitannins which exist in the cork material (namely one called vescalagin) react with the catechins present in the wine, producing, among others, Acutissimin A, which is an anti-tumoural agent about 250 times more potent than one of the most common anti-cancer drugs clinically used (VP-16). So, the contact of wine samples without the barrel winemaking stage (oak contact) was carried out with cork in order to determine the presence of Acutissimin A. After a contact time of about 30 min, 150 min and 6 days, Acutissimin A was detected in all samples containing cork. In the samples in which the contact was with oak wood, in our conditions, it was not possible to detect Acutissimin A.
The following values have no corresponding Zotero field: pub-location: 42 RUE MARSAN, 33300 BORDEAUX, FRANCE publisher: VIGNE ET VIN PUBLICATIONS INT
Keywords: acutissimin A; Cork; HPLC/MS; identification; oak; wine

Effects of the interaction between drought and shade on water relations, gas exchange and morphological traits in cork oak (Quercus suber L.) seedlings - Aranda, I.; Castro, L.; Pardos, M.; Gil, L.; Pardos, J. a (Forest Ecology and Management, 2005)
The combined effect of drought and light on different physiological and biochemical traits was assessed in cork oak (Quercus suber L.) seedlings grown under two levels of light availability and submitted to a long-standing drought. Watering was withdrawn after germination and seedlings were allowed to dry to a water content of ca. 50% of ﬁeld capacity. At this point, water-stressed seedlings were grown under moderate drought and two light regimes: high light (HL—50%) and low light (LL— 2%). Soil water in control plants was kept close to ﬁeld capacity (90–100%) for both light environments. Water-relations parameters derived from P–V curves, gas exchange and water status at predawn (Cpd ) were evaluated at twice during the experiment. Nitrogen and chlorophyll contents were determined in the same leaves used for the gas exchange measurements. In addition, maximum rate of carboxylation (Vcmax) and electronic transport (Jmax) were derived from A–Ci curves in well-watered seedlings. The variation on moisture availability during the experiment was the same under both light environments. In control plants, Cpd was over 0.3 MPa at the two harvests, while stressed seedlings decreased to 0.9 MPa, with no differences between light treatments. Water stress decreased osmotic potentials at full (Cp100 ) and zero turgor (Cp0 ). The regressions between both potentials and Cpd showed a higher intercept in shade grown seedlings. This fact will point out the higher osmoregulation capacity in sun seedlings whatever water availability. Nitrogen investment on a per leaf mass (Nmass ), chlorophyll content (Chlmass ) and SLA tended to show a typical pattern of sun-shade acclimation. Thus, the three parameters increased with shade. Only for Nmass there was a signiﬁcant effect of watering, since water stress increased Nmass . LL plants showed a lower photosynthetic capacity in terms of maximum net photosynthesis at saturating light (Amax), which was related to a decrease in Vcmax and Jmax . Both parameters varied with speciﬁc leaf area (SLA) in a similar way. The low-light environment brought about a higher nitrogen investment in chlorophyll, while under high-light environment the investment was higher in carboxylation (Vcmax) and electronic transport ( Fmax). Stomatal conductance to water vapour (gwv ) and Amax were lower in low-light seedlings independently of watering. In addition, there was a trend to keep higher intrinsic water use efﬁciency (IWUE) under high light environment. The increase of IWUE under water stress was higher in HL seedlings. This was as consequence of the steeper decline in gwv as Cpd decreased. The decrease of Amax with Cpd occurred in a similar way in LL and HL seedlings. Thus, the HL seedlings tended to sustain a higher ability to increase IWUE than LL seedlings when they were submitted to the same water stress.
Keywords: Cork oak; Drought; light; osmotic adjustment; photosynthesis; water use efficiency

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M.; Royo, A.; Gil, L.; Pardos, J. A. (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.6710.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)

Análisis de la variabilidad de adn de cloroplastos en Quercus ilex L., Q. suber L. Y Q. coccifera L.. - COLLADA, C.; JIMÉNEZ, P.; Gil, L. (III Congreso Forestal Español, 2001)
Chloroplast (Cp) and mitochondrial (mt) DNA variation have been studied by PCR-RFLP in 14 location (13 with Q. suber, 12 with Q. ilex and 6 with Q. coccifera) along the natural distribution area of these species in the Iberian Peninsula. Five chloroplast DNA primers pairs and one mitochondrial DNA primer pair have been used, each one in combination with a restriction enzyme. 29 different haplotypes have been detected, In the case of Q. suber a characteristic haplotype, very divergent of the remaining ones has been described. Usually, species don’t share haplotypes within the same populations. The distribution of haplotypes suggests a geographical structuring. The levels of genetic differentiation are similar to those obtained in oaks.hS is significantly higher in Q. ilex (hS=0,262). Differentiation coefficients (Gst) are similar in the three species and indicate a high typical structuring of maternal markers.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: chloroplast DNA; differentiation; geographic distribution; Haplotypes; phylogeny; Quercus

Relaciones hídricas en procedencias de QUERCUS SUBER L. - Castro, L.; Aranda, I.; Gil, L.; Pardos, J. A. (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso
Keywords: Cork oak; osmotic adjustment; pressure-volume curves; water potential